PENGARUH GOOD CORPORATE GOVERNANCE (GCG), ASIMETRI INFORMASI, UKURAN PERUSAHAAN, LAVERAGE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (PERIODE 2011-2012) - -, Darmawan; -, Desmiyawati; -, Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research is to explore the influence of institutional ownership, managerial ownership, audit committee, audit reputation, information asymetry, firm size, laverage to earning management in manufacturing company. The semple of this researchs is manufacturing company listed onthe Indonesia Stock Exchange period2011-2012. The sampling design of this research is purposive sampling with the final sample 60 companies. The data analysis technique used in this research is classical assumption test (normality, multicollinearity, autocorrelation, and heteroscedasticity) and multiple regression. The results of this research showed that institutional ownership, audit reputation, firm size, and laverage influence toearning management, while managerial ownership, audit committee, and information asymmetry does not influence the earning management.Keywords: Good Corporate Governance (GCG), Information Asymetry, Firm Size, Laverage, Earning Management.